Decolonizing Bureaucracy in Papua: Indigenous Logics, Institutional Hybridity, and the Limits of Special Autonomy - Sarjito, Aris; Mursidi, Mursidi (CV Insan Kreasi Media, 2025)
Two decades after the implementation of Special Autonomy (Otsus), Papua remains one of Indonesia’s most underdeveloped regions. Although the policy introduced fiscal decentralization and recognized indigenous rights, it has failed to reform bureaucratic structures in ways that reflect local socio-cultural realities. This study explores the institutional disconnect between national administrative models and indigenous governance systems through a qualitative-descriptive analysis of secondary data. Findings show that the absence of structural integration, along with the symbolic role of bodies like the Majelis Rakyat Papua (MRP, undermines the legitimacy and effectiveness of governance. Meanwhile, customary logics based on restorative justice, consensus leadership, and clan-based redistribution remain active but excluded. The paper advocates a hybrid governance model that incorporates indigenous institutions as legitimate partners in public administration. Drawing from Melanesian practices and localized policy analysis, the study proposes a framework for partial institutional integration that balances formal state function with cultural legitimacy.